Berganês, a new sheep breed from the Brazilian semiarid: performance and carcass traits in different sex-classes by univariate and multivariate approaches - Silva Filho, José Renaldo Vilar da; Moura Neto, João Bandeira de; Chagas, Ellio Celestino de Oiveira; Santos, Lays Thayse Alves dos; Souza, José Ilson Rodrigues de; Queiroz, Mário Adriano ávila; Rodrigues, Rafael Torres de Souza; Voltolini, Tadeu Vinhas (Acta Scientiarum. Animal Sciences, 2023)
Twenty-four lambs between four and five months of age were divided into sex classes: uncastrated males, castrated males and females, eight for each treatment, with an average body weight of 27.00 ± 3.13 kg. dry matter and water intakes were higher for uncastrated males (p < 0.001). final body weight, body weight at slaughter, average daily gain and cold carcass weight were greater for uncastrated, intermediate for castrated and lower for females (p < 0.05). hot and cold carcass yields were higher for castrated males and females, respectively. (p < 0.05). based on principal component analysis, twenty-five variables were selected out of thirty-two, in some of the seven principal components generated, summarizing 21.87% data dimension. Discriminant analysis identified greater discrimination power for body weight at slaughter, thorax width, thorax depth, fatness, dry matter intake and hot carcass weight. All lambs were classified into their respective sex classes. Therefore, uncastrated males have performed better than castrated ones and both showed higher performance than females. Females and castrated males showed higher carcass yield. Discriminant analysis indicated heterogeneity between sex classes.